2021
DOI: 10.3389/fphys.2021.661030
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Anatomorphological Features of the Portal Venous System on Postsplenectomy Hemodynamic Characteristics in Patients With Portal Hypertension: A Computational Model-Based Study

Abstract: Splenectomy, as an effective surgery for relieving complications caused by portal hypertension, is often accompanied by a significantly increased incidence of postoperative thrombosis in the portal venous system (PVS). While the underlying mechanisms remain insufficiently understood, the marked changes in hemodynamic conditions in the PVS following splenectomy have been suggested to be a potential contributing factor. The aim of this study was to investigate the influences of the anatomorphological features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…where u$\vec{u}$ and p represented the fluid velocity vector and pressure, respectively; ρ represents a fluid density of 1060 kg/m 3 and μ represents a fluid viscosity of 0.0045 Pa s 18,20 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…where u$\vec{u}$ and p represented the fluid velocity vector and pressure, respectively; ρ represents a fluid density of 1060 kg/m 3 and μ represents a fluid viscosity of 0.0045 Pa s 18,20 …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the following models with different geometric morphological parameters were established in this study, and only morphological parameters changed on the basis of type 1 anatomical structure were shown: (1) Only the distance between IMV and PV (Figure 1b); (2) Only the angles of IMV and SV are changed (Figure 1c); (3) Only the angles of PV and SV are changed (Figure 1d); (4) Only the curvature of SV is changed (Figure 1e). 18 And on these basic models, the D SV increases by 1 mm, from 8 to 12 mm.…”
Section: Ideal Modelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some previous studies employed computational models to address various issues related to the portal venous system such as the diagnosis of portal hypertension ( Wang et al, 2017 ; Wang et al, 2018 ; Wang et al, 2020 ) and the hemodynamic changes due to cirrhosis ( George et al, 2015 ; Wei et al, 2017 ). In our previous study, the influence of anatomorphological features of the portal venous system on post-splenectomy hemodynamic characteristics was investigated based on idealized computational models ( Wang et al, 2021 ). Moreover, we also conducted a proof-of-concept study that preliminarily indicated the association between hemodynamic metrics and post-splenectomy thrombosis based on three patient-specific models ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The marked changes in hemodynamics in cirrhosis have been suggested to be a potential contributing factor to the formation of PVT. When the portal vein (PV) velocity decreases to 15 cm/s, patients with cirrhosis have a highly significant risk association with the future development of PVT [ 11 ], and the changes in hemodynamic characteristics after splenectomy increase the risk of PVT development [ 12 , 13 ]. While the anatomical structure of the portal venous system plays a significant role in the development of its flow features and hemodynamic parameters.…”
Section: Introductionmentioning
confidence: 99%